Operational Performance and Weld Bead Characteristics of Experimental Tubular-Wires for Underwater Welding - Castellanos-Gonzalez, Orlando M.; Sanchez Lobo, Eduardo J.; Fydrych, Dariusz; Cota, Bruno Silva; Júnior, José Gedael Fagundes [UNESP]; Moreno-Uribe, Andrés Mauricio (Wydawnictwo Naukowe Gabriel Borowski (WNGB), 2024)
Aiming to evaluate new formulations and their operational behavior underwater, two experimental tubular wires with different chemical compositions in their internal flux were initially manufactured, employing a pilot machine and a unique manufacturing process. Weld beads were deposited on a plate placed in a flat position inside a tank using a mechanized system and the IMC 300 welding power source. The work was done at a depth of 0.3 meters of water, and both reverse and direct polarities were used. Arc voltage at 28 V, wire feed speed at 4.5 m/min and welding speed at 250 mm/min were maintained in all experiments. As a result, the weld bead morphology and the electrical variables related to arc voltage and welding current were analyzed. It was concluded that the metal transfer showed a predomi-nance of short circuits and a decrease in the average value of the Short Circuit Index by 67% when using the positive polarity configuration compared to the negative polarity. Moreover, the average penetration value was 38 % higher for the oxidizing-based tubular wire than for the rutile-based tubular wire, which has a possible relationship with the more significant presence of oxygen in the flux. In addition, the results present an analysis of the performance of the process and the characterization of the weld beads obtained to guide possible modifications in the parameters.
Keywords: electric arc welding; flux-cored arc welding; polarity; PTFE; underwater wet welding